Robert R. Williams papers - Williams, Robert R., 1886-1965.
Correspondence, diaries (1938-1953), affidavits, reports, subject files, laboratory notebooks, speeches and writings, printed matter, and other papers relating to Williams's research in nutritional chemistry, especially his work on the development of Vitamin B1 (thiamin) while searching for a cure for beri-beri. Other topics include his affiliations with Merck & Company, IG Farben (Interessengemeinschaft Farbenindustrie Aktiengesellschaft), the Research Corporation, and the Carnegie Corporation of New York; patent disputes; his travels in the southern states and in Asia to promote dietary enrichment by the addition of thiamin to flour and rice; and the establishment of the Williams-Waterman Fund for the control of dietary diseases. Correspondents include Edwin R. Buchman, Joseph K. Cline, Casimir Funk, M.C. Kik, E.J. Lease, John C. Merriam, Howard Andrews Poillon, and Robert E. Waterman.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Chemist and nutritionist.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Buchman, Edwin R. -- Correspondence; Cline, Joseph K. -- Correspondence; Funk, Casimir, -- 1884-1967 -- Correspondence; Kik, M. C. -- 1896-1975 -- Correspondence; Lease, E. J. -- 1908- -- Correspondence; Merriam, John C. -- 1869-1945 -- Correspondence; Poillon, Howard Andrews, -- 1879-1954 -- Correspondence; Waterman, Robert E. -- 1899- -- Correspondence; Carnegie Corporation of New York; Interessengemeinschaft Farbenindustrie Aktiengesellschaft; Merck & Co; Research Corporation; Williams-Waterman Fund; Beri-beri.; Diet -- Asia; Diet -- Southern States; Enriched foods; Flour; Food -- Composition; Nutrition; Nutritionally induced diseases; Patents; Rice; Vitamin B in human nutrition; Vitamin B1.; Asia -- Description and travel; Southern States -- Description and travel; Chemists; Nutritionists